Comparison of Growth Factor Treatments on the Fibrochondrogenic Potential of Canine Fibroblast‐Like Synoviocytes for Meniscal Tissue Engineering. Issue 6 (11th March 2014) - Spina, Jason; Warnock, Jennifer; Duesterdieck‐Zellmer, Katja; Baltzer, Wendy; Ott, Jesse; Bay, Brian
<x xml:space="preserve">Abstract</x> Objective To determine the in vitro effects of differing growth factor treatments on the fibrochondrogenic potential of fibroblast‐like synoviocytes from cruciate ligament deficient femorotibial joints of dogs. Study Design In vitro study. Sample Population Synoviocytes from dogs (n = 8) with naturally occurring cruciate ligament insufficiency. Methods Synoviocytes were cultured in monolayer and synthesized into tensioned synoviocyte bioscaffolds (TSB) suspended in media containing TGF‐β3, or FGF‐2, TGF‐β1, and IGF‐I. The 1, 9‐dimethylmethylene blue (DMMB) assay and toluidine blue stain assessed glycosaminoglycan content; hydroxyproline assay, and collagen I and II immunohistochemistry assessed collagen content. Biomechanical properties were determined by materials testing/force–deformation curves. Results All tissue cultures formed tensioned fibrous tissue‐like constructs. Mean tissue cellularity and cellular viability was significantly greater in the triple growth factor‐treated TSB by 0.09% and 44%, respectively. Percentage collagen content, and relative gene expression for collagen I, II, and aggrecan was not significantly different between groups. Median percentage of GAG content was significantly greater in triple growth factor‐treated TSB by 1.6%. Biomechanical properties were not different in compression. Triple growth factor‐treated TSB were significantly stronger in toughness, peak load to failure, and stiffness in tension. Conclusions TGF‐β3 cultured bioscaffolds failed to outperform triple growth factor‐treated TSB. Architectural extracellular matrix (ECM) organization and cellularity likely explained the differences between groups. TGF‐β3 alone cannot be recommended at this time for in vitro formation of autologous fibrocartilage bioscaffolds for meniscal deficiency.